The prevalence and genotype of 21-hydroxylase deficiency in the Croatian Romani population - Dumic, Katja K.; Grubic, Zorana; Kusec, Vesna; Braovac, Duje; Gotovac, Kristina; Vinkovic, Maja; Vucinic, Maja; Dumic, Miroslav (Frontiers in Endocrinology, 2023)
Objective Congenital adrenal hyperplasia (CAH) owing to 21-hydroxylase deficiency (21-OHD) is a rare autosomal recessive disorder caused by pathological variants in the CYP21A2 gene. After a high prevalence of classic 21-OHD CAH in the Romani population was reported in the Republic of North Macedonia, we decided to estimate the prevalence of 21-OHD in Croatia and, if high, assess the possible causes and estimate the frequency of particular CYP21A2 variants. Design Cross-sectional study. Methods Data from a Croatian 21-OHD genetic database was reviewed, and only Romani patients were included in the study. CYP21A2 genotyping was performed using allele-specific PCR, MLPA, and Sanger sequencing. Results According to a survey conducted in 2017, Croatia had 22,500 Romani people and six of them had a salt-wasting (SW) form of 21-OHD. All were homozygous for the c.IVS2-13A/C-G pathological variant in intron 2 and descended from consanguineous families belonging to different Romani tribes. The calculated prevalence of 21-OHD in Croatian Romani is 1:3,750, while in the Croatian general population, it is 1:18,000. Three of the six Romani patients originated from two neighboring villages in North-western Croatia (Slavonia County), as well as the seventh patient who is of mixed Romani/Croatian descent and heterozygous for the c.IVS2-13A/C-G pathological variant (not included in the prevalence calculation). Conclusion A high prevalence of SW 21-OHD in the Croatian Romani population caused by the homozygous cIVS2-13A/C-G pathological variant was found. In addition to isolation and consanguinity, other possible reasons could be the heterozygous advantage of the CYP21A2 gene pathological variant and the bottleneck effect as a result of the Romani Holocaust in World War II.